Biologically active alkaloids from Alstonia angustiloba / Ku Wai Foong - Ku, Wai Foong (2011)
The alkaloidal content of Malaysian plant, Alstonia angustiloba Miq., was investigated and the results are summarized as below (Table). A total of 20 alkaloids were isolated and characterized, of which, three were new alkaloids, viz., angustilobine C (1), andransinine (2), and angustiphylline (3). Angustilobine C (1) and andransinine (2) are alkaloids of the angustilobine- and andranginine type, respectively, while angustiphylline (3) is a new bisindole alkaloid constituted from the union of uleine and secovallesamine moieties. Alkaloids 1 and 2 were obtained from the leaf extract while the bisindole 3 was isolated from the bark extract. In addition to the new alkaloids, seventeen known alkaloids were also obtained which were: 19,20-E-vallesamine (4), 17-O-acetylvallesamine (5), yunnannensine (6), angustilobine A (7), angustilobine B (8), nor-6,7-secoangustilobine B (9), nor-6,7-seco-19,20-epoxyangustilobine B (10), undulifoline (11), condylocarpine (12), 20S-tubotaiwine (13), N(4)-demethylechitamine (14), 17-O-acetyl-N(4)-demethylechitamine (15), alstolucine B (16), vincamine (17), 16R,19E-isositsirikine (18), venoterpine (19), and cantleyine (20). Angustilobine C (1) showed moderate cytotoxicity towards both drug-sensitive and vincristine-resistant KB cells (IC50 7.76 and 7.33 g/mL, respectively), while andransinine (2) reversed multidrug resistance in vincristine-resistant KB cells (KB/VJ300 cells, IC50 1.61 g/mL in the presence of 0.1 g/mL of vincristine).